Kedisiplinan Pemakaian APD Pada Karyawan Yang Mendapat Penyuluhan K3 Bagian Produksi Di PT. Iskandar Indah Printing Textile - Santoso, Wisnu Budi, Tarwaka, PGDip, Sc, M. Erg, Tri Puji Kurniawan, SKM, M. Kes (2016)
Advanced Industrial development occurs in all sectors, including textile industry. Every working place has various danger or risk factors that can affect occupational safety andhealth. Level of safety depends on attitude and practices of employees and employers. Therefore, nlightenment activity is very important to improve occupational safety and accident prevention. Purpose of the research is to know difference discipline the use of Personal Protective Equipment who were not given ccupational safety and health enlightenmentworkers and who are given occupational safety and health enlightenment workers among production of PT. Iskandar Indah printing Textile. The research was a quasi-experimental one equipped with quantitative approach. The research used on-equivalent control group design. Population of the research iswho were not given occupational safety and health enlightenmentproductionworkers amounting to 15 individuals and who are given occupational safety and ealthenlightenment production workers amounting to 15 individuals. Sample was taken by using random sampling technique. Statistical test of Mann-Whitney obtained p-value = 0.015<0.05. It means that difference discipline the use of Personal Protective Equipmentwho were not given occupational health and safety enlightenmentworkersand who are given occupational health and safety enlightenment workersamong production of PT. Iskandar Indah printing Textile.